Contributions of Human Rights Education (HRE) and Participatory Action Research (PAR) in Contexts of Community Work - Cubillos-Vega, Carla (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This work explores the community, political, and ethical dimensions of Social Work and their connection with human rights education and participatory practices, particularly participatory action research, and their confluence in a common goal: promoting the emancipation of people and groups. The study explores critical human rights education and participatory action research as strategies to be used in the practice of Social Work with communities in the defense and promotion of human rights. Thus, realistic possibilities to promote, defend and enforce human rights in and by the communities are explored. These strategies are presented together with tools to integrate human rights in quotidian life.